The Effect of Flash Sale and Free Shipping Tagline on Interest to Buy at Shopee at Students of Muhammadiyah University Surakarta - Nafisa, Adinda Alfin; Suranto, S (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to analyze the effect of flash sales and the free shipping tagline on buying interest at Shopee among Muhammadiyah University students in Surakarta. The population in this study is Muhammadiyah University Surakarta students who use the Shopee application. The type of research used is quantitative research using a survey design, the sample used in this study amounted to 100 respondents. Data collection techniques and instruments in this study used a questionnaire conducted via the Google form . The data analysis technique used is multiple linear regression analysis, t test, f test, coefficient of determination. The results of the data analysis revealed that the flash sale variable had a significant effect on the purchase intention of students at the Muhammadiyah University of Surakarta. This can be proven from the results of the t test where the t count value is 4.733 greater than t table 1.985. The tagline variable has no significant effect on buying interest in Muhammadiyah Surakarta University students. This can be proven from the results of the t test where the t count value is 1.776 which is smaller than the t table 1.985. Flash sale variables and taglines have an effect on buying interest among Muhammadiyah Surakarta University students. This is evidenced by the results of the f test where the sign value is 0.000 <0.05 and the calculated f value is 112.000 > 3.09 . Study This prove that the flash sale and the tagline have role positive in increase Power buy student University Surakarta Muhammadiyah.